2012
DOI: 10.1098/rstb.2011.0188
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for biased co-transmission of speciation islands inAnopheles gambiae

Abstract: Genome-scale scans have revealed highly heterogeneous levels of divergence between closely related taxa in many systems. Generally, a small number of regions show high differentiation, with the rest of the genome showing no or only low levels of divergence. These patterns have been interpreted as evidence for ongoing speciation-with-gene-flow, with introgression homogenizing the whole genome except loci involved in reproductive isolation. However, as the number of selected loci increases, the probability of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 66 publications
(97 reference statements)
1
50
0
Order By: Relevance
“…This point is exemplified in the empirical patterns described in this issue by Hahn et al [29] and the new theoretical results on expected coalescent patterns for neutral loci within chromosomal inversions reported by Guerrero et al [41]. Rather than casting despair, this simply highlights a clear avenue for further work.…”
Section: Causes Of Patterns Of Genomic Divergencementioning
confidence: 81%
See 1 more Smart Citation
“…This point is exemplified in the empirical patterns described in this issue by Hahn et al [29] and the new theoretical results on expected coalescent patterns for neutral loci within chromosomal inversions reported by Guerrero et al [41]. Rather than casting despair, this simply highlights a clear avenue for further work.…”
Section: Causes Of Patterns Of Genomic Divergencementioning
confidence: 81%
“…These patterns quantified by 'genome scans' of numerous loci provide the empirical observations on which our current understanding of genomic divergence is based. Numerous studies in this issue present new empirical data or summarize the literature on how genetic differentiation is distributed throughout the genome [25][26][27][28][29][30][31][32][33]. The authors relate these patterns to the island metaphor to try and draw inferences concerning the significance of genome architecture and the processes facilitating speciation.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have used multiple restriction fragment length polymorphism assays and/or mismatch primer-based SNP assays to genotype one SNP in each of the three (X, 2L, and 3L) islands of divergence (26,36). We extended this approach with the development of the DIS assay (35) to describe A. gambiae populations throughout West Africa ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…White et al (26) reported nearly complete LD between the three islands of divergence in natural populations. Hahn et al (36) used laboratory crosses to demonstrate a lack of intrinsic incompatibilities that might explain this association. Based on these observations, it was proposed that the association among the three islands is maintained by near-complete RI between M and S forms in nature.…”
Section: Resultsmentioning
confidence: 99%
“…While there are reports of simpler genetic architectures of divergence, at least in some instances (especially early studies), scan resolution appears to have been too low to detect smaller islands of divergence (for example, Hahn et al 32 ).…”
Section: Discussionmentioning
confidence: 99%